Effect of Bioremediation on early seedling growth of Amaranthus hybridus L. grown on palm oil mill effluent polluted soil - Okon Godwin, Okon; Elijah, Glory (International Journal of Biological Research, 2014)
The effect of Bioremediation on Early Seedling growth of Amaranthus hybridus L. on oil palm effluent polluted soil was carried out in the field using perforated polythene bags. The soil samples were polluted with 0, 80, 120 and 240ml of oil palm effluent and amended with compost manure supplement (fermented oil palm spikelet) at 0, 40, 60 and 80 g respectively). The 0ml and 0g served as controls. The mean result obtained after 12 weeks showed that the addition of compost manure supplement (fermented oil palm spikelet) to the contaminated soil promotes growth of plant as there was increase in the growth parameters such as shoot height, petiole length, leaf area, number of nodes, number of branches, internode length, root length, and moisture content. This study recommends that contaminated soils should be amended with manure to improve the growth performance of plants. Keywords: Amaranthus, Bioremediation, Effluent, Palm Oil, Pollution and POME.